Extreme Flexibility in a Zeolitic Imidazolate Framework: Porous to Dense Phase Transition in Desolvated ZIF-4 - Wharmby, Michael T.; Henke, Sebastian; Bennett, Thomas D.; Bajpe, Sneha R.; Schwedler, Inke; Thompson, Stephen P.; Gozzo, Fabia; Simoncic, Petra; Mellot-Draznieks, Caroline; Tao, Haizheng; Yue, Yuanzheng; Cheetham, Anthony K. (Angewandte Chemie International Edition, 2015)
Desolvated zeolitic imidazolate framework ZIF‐4(Zn) undergoes a discontinuous porous to dense phase transition on cooling through 140 K, with a 23 % contraction in unit cell volume. The structure of the non‐porous, low temperature phase was determined from synchrotron X‐ray powder diffraction data and its density was found to be slightly less than that of the densest ZIF phase, ZIF‐zni. The mechanism of the phase transition involves a cooperative rotation of imidazolate linkers resulting in isotropic framework contraction and pore space minimization. DFT calculations established the energy of the new structure relative to those of the room temperature phase and ZIF‐zni, while DSC measurements indicate the entropic stabilization of the porous room temperature phase at temperatures above 140 K. ZIF‐4(Zn) undergoes a porous to non‐porous transition on cooling from the high‐temperature (HT) to low‐temperature (LT) phase. The nature of this transition is elucidated by a combined approach of structure solution from powder diffraction, DSC measurement, and DFT calculations.